Corporate foresight and innovation management: A portfolio-approach in evaluating organizational development - von der Gracht, Heiko; Vennemann, Christoph Robert; Darkow, Inga-Lena (Futures, 2010)
The transition from a traditional industry-driven economy to a knowledge-based economy requires new concepts and methods for companies to sustain competitive advantage. Here, academia has identified corporate foresight and innovation as key success factors. While, content-wise, the contribution of futures research methods to the innovation process has already been researched, this study strives to explore the status quo of organizational development stages of both concepts. To do so, we developed a portfolio-approach, the so-called ‘Future-Fitness-Portfolio’, which enables companies to qualitatively compare amongst others and identify organizational improvement potential. In addition, we conducted expert interviews to explore future organizational development trends in corporate foresight and innovation management. As our research revealed, five strategic clusters can be identified within the portfolio. Consequently, we propose specific strategies for each individual cluster. We conclude that there will be two main organizational development trends for corporate foresight and innovation management in the future: in traditional industries with conventional business models and long product-life-cycles, companies will follow a different development path than companies in dynamic industries with innovative business models and short product-life-cycles.